A survey of the perceptions of lecturers and English Second Language students regarding ESL students' language-related problems at Technikon Natal - Johnston, Graham Francis (Rhodes University, Faculty of Education, Department of Education, 1993)
The shortage of manpower in South Africa with technological skills is a widespread problem. Technikons are under extreme pressure to develop these skills in the student population. Admission statistics at Technikon Natal show a marked increase in ESL students enrolling in a wide variety of national diploma courses. The inadequate education received by the majority of ESL students in South Africa has not prepared them for the demands of tertiary education. As English is the medium of instruction at Technikon Natal, underdeveloped language skills tend to hinder the students' progress. Technikon Natal is currently considering an Educational Development Strategy designed to assist students. In order for a response to perceived language-related problems to be meaningful, a survey of such issues was considered a practical starting point to establish that these issues were in fact problematic. The survey was intended to probe certain perceptions held by students and staff regarding attitudes, which might have been preconceived. It also provided clarification that some of these perceptions are inaccurate, and in some cases, incorrect. In addition to this, it established that there is considerable support among students and staff for departmentally-integrated support programmes. In terms of Technikon Natal's present position on an ESL educational development continuum, the findings indicate that much benefit could be derived from the research carried out in other tertiary institutions with regard to academic support programmes. Areas in which there was a considerable disparity of views held were identified and commented upon. In conclusion, it was felt that attention should be focussed on the following: recognition of the need for an integrated ESL programme; departmental reinforcement of academic skills; decentralisation of the ASP programme. The survey concludes with a brief comment on current developments in response to ESL needs at Technikon Natal.
Keywords: English language -- Study and teaching -- South Africa -- Foreign speakers; Compensatory education -- South Africa; High school graduates -- South Africa